(untitled) (Bangladesh Journal of Medical Science, 2016)
Malnutrition is a common but frequently overlooked problem among patients with cirrhosis of liver. Malnourished cirrhotic patients have a higher rate of complications and an overall increased mortality. Identifying these patients is of great clinical importance. This study was carried out to assess nutritional status of cirrhotic patients to identify those who are malnourished and to see the relationship between severity of liver disease and malnutrition. 105 patients were selected by purposive type sampling. Nutritional status was assessed by 3 anthropometric assessment tools- body mass index (BMI), mid upper arm muscle circumference (MAMC) and triceps skin fold thickness (TST). Severity of liver disease was assessed by Child-Pugh (CP) score. Severe malnutrition was defined as MAMC and TST <5th percentile, calculated from standard tables, and as BMI <16. Among 105 patients 18, 49 and 38 were of Child-Pugh group (CP group) A, B and C respectively. Anthropometric assessment revealed that, when assessed by MAMC 63% of the study population were severely malnourished. Based on MAMC, severe malnutrition was present in 39%, 63% and 73% patients in CP group A, B and C, respectively (P<0.05). So, percentage of severely malnourished patient increased with the increase in severity of liver disease. Based on TST, 28%, 34% and 50% patients were severely malnourished in CP-A, CP-B and in CP-C (p>0.05) respectively which showed a trend similar to that by MAMC. Whereas, based on BMI, 0%, 8% and 2% patients were severely malnourished respectively (p>0.05). It showed a decrease in the percentage of severely malnourished patient in CP group C than in CP group B. In this study, nutritional assessment by TST and MAMC revealed that severe malnutrition was common in our study population and assessment by MAMC showed a statistically significant association of severity of liver disease with severe malnutrition. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.189-194